Seminal Attributes And Their Relation With Scrotal Biometry And Sexual Behaviour Of Murrah Buffalo Bull - Singh, A.K.; Shukla, S.P.; Pandey, S.S.; Misraulia, K.S.; Kumar , Sudarshan (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted on 32 Murrah buffalo bulls to evaluate the seminal attributes and their relation with scrotal biometry and sexual behavior of Murrah buffo bull . There was significant (P
Keywords: Murrah buffalo; Scrotal circumference; Sexual behaviour; Sperm motility